PENGARUH SUPERVISI DAN MOTIVASI KEPALA SEKOLAH TERHADAP KINERJA TENAGA PENDIDIK - Adam Saleh (STAI Nurul Falah Airmolek, 2018)
Headmaster’s supervision is an activity of quidance to increase teacher’s ablity and performance in implementing his duty, so that the learning process runs effectively and efficiently. whereas teacher’s motivation is an inner or outer support to get the good spiritof teaching.